2011
DOI: 10.5194/nhess-11-273-2011
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the tsunami catalogue affecting Turkish coasts and surrounding regions

Abstract: Abstract. The coasts of Turkey have been hit by tsunamis in the past. The first national earthquake-tsunami catalogues were compiled in the early 1980s while the most up-to-date tsunami catalogues are mainly the products of recent European projects. The EU projects GITEC and GITEC-TWO (Genesis and Impact of Tsunamis on the European Coasts) and TRANSFER (Tsunami Risk ANd Strategies For the European Region) have added important contributions in establishing and developing unified criteria for tsunami parameteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 60 publications
1
67
0
4
Order By: Relevance
“…9). This date coincides with the AD 110 and AD 115 Antioch Earthquakes in literature (Altınok et al, 2011;Erel and Adatepe, 2007;Sbeinati et al, 2005). In the same literature, it is specified that the intensities of AD 110 and AD 115 Antioch Earthquakes were respectively 8 and 9, and 260,000 people died as a result of these earthquakes.…”
Section: Sakarlakmentioning
confidence: 96%
“…9). This date coincides with the AD 110 and AD 115 Antioch Earthquakes in literature (Altınok et al, 2011;Erel and Adatepe, 2007;Sbeinati et al, 2005). In the same literature, it is specified that the intensities of AD 110 and AD 115 Antioch Earthquakes were respectively 8 and 9, and 260,000 people died as a result of these earthquakes.…”
Section: Sakarlakmentioning
confidence: 96%
“…The earliest historically documented tsunamigenic earthquake in this region occurred in 330 BC around Lemnos Island, a mere 220 km SE (Altinok et al 2009(Altinok et al , 2011Soloviev et al 2000). This large magnitude earthquake is thought to have resulted in the disappearance of Chrysi Island and the Moschylos volcano (Soloviev et al 2000) with tsunami deposits reported from the Turkish coast some 180 km NE (Altinok et al 2013).…”
Section: An Alternative Hypothesis For the Interpretation Of Mass Burmentioning
confidence: 99%
“…); (2) mass wasting and creep (Zitter et al, 2012;Shillington et al, 2012); (3) deep sedimentation specificities Sari and Çagatay, 2006;Çagatay et al, 2012;Drab et al, 2012); and (4) detection and dating of historical coseismic scarps (Armijo et al, 2005;Uçarkuş, 2010). Historical tsunami reports and modeling (Altinok et al, 2011;Hébert et al, 2005) complete these different data, taking into account the fact that these phenomena are not systematically associated with Armijo et al (2002Armijo et al ( , 2005, and GPS kinematics from McClusky et al (2000) and Reilinger et al (2006). earthquakes .…”
Section: Structural Setting and Recent Seismic Activitymentioning
confidence: 99%